URIC ACID IN ACUTE CORONARY SYNDROME: CORRELATIONS WITH IN-HOSPITAL MORTALITY AND COMPLICATIONS. (April 2021) - Maloberti, Alessandro; Rebora, Paola; Morici, Nuccia; Sacco, Alica; Viola, Giovanna; Lattuada, Francesca; Molinari, Valentina; Occhi, Lucia; Bassi, Ilaria; Portoghese, Alessandro; Fortina, Matteo; Oliva, Fabrizio; et al.
Abstract: Objective: Uric acid (UA) has been related to in-hospital mortality in ACS patients. Furthermore, it has been related to early relapse of non-fatal cardiovascular events and to intermediate outcome such as use of intra-aortic balloon pump, noninvasive ventilation, longer inward stay, bleeding but also clinical presentation with AF or Heart Failure (HF). Aim of the study was to evaluate the role of UA as a possible determinants of primary (in-hospital mortality) and secondary outcomes considered as variables indicative of in-hospitale complications (myocardial re-infarction, in-stent thrombosys, bleeding, stroke), worst clinical presentation (presentation with HF or AF, admission EF, three vessels coronaric involvement at the coronary angiogram), in-hospital complication (inotropes, intra-aortic balloon pump and non-invasive ventilation uses during hospital stay) and worst recovery (discharge EF). Design and method: retro-prospective cohort study of 563 patients admitted for ACS at the Cardiological Intensive Care Unit of the Niguarda Ca' Granda Hospital. Cox regression analysis was performed to evaluate the association between UA and primary and seconday outcome adjusted for the following covariates: age, gender, previous myocardial infarction, arterial hypertension, Charlson Comorbidity Index and creatinine. Results: mean age was 66.5 ± 12.3 years, 79.2% of the patients were males and 49.9% of the ACS were STEMI. Hyperuricemic subjects were older, with more prominent cardiovascular risk factor and previous myocardial infarction. Furthermore, they more frequently died during hospital stay, they present more frequently heart failure and AF as clinical presentation, have more commonly three vessels disease and use more frequently intra-aortic balloon pump and non-invasive ventilation. Finally, also EF at admission and discharge were lower in hyperuricemic patients. At multivariate analysis UA was a significant determinants of primary and secondary outcomes (except for three vessels coronaric disease, bleeding, stroke, re-infaction and in-stent thrombosys). Conclusions: in conclusion UA is an independent determinants of in-hospital mortality and a variables suggestive of worst clinical presentation, in-hospital complications and worst recovery.